Sedimentary Hydrodynamic Processes Under Low-Oxygen Conditions: Implications for Past, Present, and Future Oceans - Bruni, Elena T.; Blattmann, Thomas M.; Haghipour, Negar; Louw, Deon; Lever, Mark; Eglinton, Timothy I. (Frontiers in Earth Science, 2022)
Continental margin sediments represent a major global sink of organic carbon (OC), and as such exert a key control on Earth’s climate. Today, OC burial in marine sediments mainly takes place under oxygen-rich water columns, where most OC is stabilized through intimate association with sediment grains and biogenic minerals. In prior episodes of Earth’s past, when large parts of the oceans were anoxic, the mode of sedimentary OC burial must have been very different, however. Present-day analogues indicate that surface sediments accumulating under low-oxygen water columns are often “soupy” in texture. Moreover, most OC occurs in large (100 - 2,000 μm diameter) organic and organo-mineral aggregates which, due to their low density, are prone to wave- and current-induced resuspension. Upon mobilization, these aggregates can undergo lateral transport within so-called nepheloid layers, and may be translocated hundreds of kilometres, and on timescales of thousands of years. Little is known about processes of formation, resuspension and hydrodynamic properties of these aggregates in oxygen-poor waters, or which factors control their eventual breakdown or burial. The goal of this study is to examine the drivers and biogeochemical consequences of this resuspension on OC cycling in modern, oxygen-depleted, “Semi-Liquid Ocean Bottom” (SLOB) regions. We argue that models of sediment and OM hydrodynamics and redistribution that describe sedimentation processes in oxygenated ocean waters of the modern ocean are a poor analogue for equivalent processes occurring under oxygen-deficient conditions. In the latter, we hypothesize that (a) the abundance of low-density organic-rich particles and aggregates leads to a greater propensity for sediment remobilization at low(er) shear stress, and (b) upon resuspension into low-oxygen bottom waters, remobilized OM may be subject to less degradation (less attenuation) during lateral transport, leading to efficient and widespread translocation to distal centres of deposition. We address specific aspects of the SLOB hypothesis utilizing a combination of literature and new data, focussing on the Benguela Upwelling Region as a model system.